KOMSEL PEMURIDAN KREATIF PEMUDA GBI BUKIT SION - Naftali Untung; Rafael Oktovianus Tanonggi; John Riwu Pekuwali (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2021)
The outbreak of the pandemic has reduced many activities, including discipleship programs in the Christian community. Of course, GBI Bukit Sion also faces this problem. Discipleship of the younger generation in this church is no longer even running since the beginning of the pandemic. And even though it is run, there are characters from young people who get bored easily to attend events related to spirituality that must be considered. then after analyzing the needs of the church, the author's group carried out the implementation of online cell groups with sharing, mentoring, and games methods that were able to be a solution to the discipleship problem in the pandemic era.